2015
DOI: 10.1016/j.bbrc.2014.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 responsive microRNA-126 and 149 regulate cell proliferation in prostate cancer

Abstract: MicroRNAs (miRNAs) are short (19-24 nt), low molecular weight RNAs that play important roles in the regulation of target genes associated with cell proliferation, differentiation, and development, by binding to the 3'-untranslated region of the target mRNAs. In this study, we examined the expression of miRNA-126 (miR-126) and miR-149 in prostate cancer, and investigated the molecular mechanisms by which they affect syndecan-1 in prostate cancer. Functional analysis of miR-126 and miR-149 was conducted in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 42 publications
2
40
0
1
Order By: Relevance
“…Furthermore, the ability of miRNAs to reprogram cancer cells into cells with stem cell-like properties and low malignancy potential has been previously demonstrated in colon cancer [23], therefore miRNAs could regulate the fate of cancer cells. These results are in line with our recently published study, in which we demonstrate that syndecan-1, miR-126, and miR-149 modulate cell senescence by controlling expression of SOX2, NANOG, and OCT4 [13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the ability of miRNAs to reprogram cancer cells into cells with stem cell-like properties and low malignancy potential has been previously demonstrated in colon cancer [23], therefore miRNAs could regulate the fate of cancer cells. These results are in line with our recently published study, in which we demonstrate that syndecan-1, miR-126, and miR-149 modulate cell senescence by controlling expression of SOX2, NANOG, and OCT4 [13].…”
Section: Discussionsupporting
confidence: 93%
“…We previously reported that this proteoglycan transforms androgen-dependent prostate cancer cells into androgen-independent tumors and facilitates progression [11,12]. Moreover, syndecan-1 and the miRNAs miR-126 and, 149 regulate cell proliferation through down-regulation of several stem cell factors such as SOX2, NANOG, and OCT4 [13]. Finally, syndecan-1 was detected in plasmacytoid urothelial carcinoma, an aggressive tumor [14][15][16][17][18], demonstrating that the protein is closely associated with urothelial carcinoma progression [19].…”
Section: Introductionmentioning
confidence: 94%
“…The gene serves as an anti-oncogene in colorectal cancer [35], HCC [36], laryngeal squamous cell carcinoma [37], and renal cell carcinoma [38]. In contrast, the gene functioned as an oncogene gene in T-cell acute lymphoblastic leukemia [39] and prostate cancer [40]. Hence, we may infer that hsa-mir-149 plays completely different roles across different tumor types.…”
Section: Discussionmentioning
confidence: 89%
“…Notably, miR-149-5p promotes cell proliferation. 27 Recent study revealed that miR-149-5p expression is significantly downregulated and plays an important role as a tumor suppressor 28 in some cancers, such as gastric cancer, 29 astrocytomas, 30 glioma, 31 colon, and rectum carcinoma (colorectal cancer (CRC)). 32 Overexpression of miR-149-5p was found to inhibit the viability and invasion of cells in vitro and have prognostic and therapeutic implications on CRC.…”
Section: Discussionmentioning
confidence: 99%